Wind effect of a twin‐tower super high‐rise building with weak connection. (18th May 2018) - Zhang, Lele; Cheng, Wentao; Xie, Zhuangning
Summary: An analysis and estimation method of multibalance synchronous test is established to study the wind effect of a complex super high‐rise building with weak connection. First, the frequency domain method is applied to deduce the calculation process of the wind effect of the multitower structure on the basis of the high frequency force balance (HFFB) technique. Then, the synchronous force test of HFFB is conducted on a twin‐tower super high‐rise building connected by a bridge. The wind‐induced response and loads and the interference effect between the two towers are analyzed based on the wind tunnel test data. The displacement correlation between the towers and the relative displacement of the multitower structure are investigated. Results show that the maximum and minimum relative displacements in the along‐bridge direction are 0.26 m in the along‐wind direction and −0.26 m in the crosswind direction, respectively. The channeling effect formed by the surrounding buildings is the main cause of the maximum cross‐bridge displacement. The influence of the correlation between the two towers can be ignored for the along‐bridge relative displacement. The results of the HFFB and high‐frequency pressure integral test agree with each other, thereby indicating the reliability and effectiveness of the proposed method.